toner

The toner composition with a polyester resin and amino resin shell, optimized for adhesion, addresses the issue of shell peeling in core-shell toners, maintaining low-temperature fixability and developability over time.

JP7599914B2Active Publication Date: 2024-12-16CANON KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020185497
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-06
Publication Date
2024-12-16
Estimated Expiration
2040-11-06

AI Technical Summary

Technical Problem

Existing toners face challenges in maintaining low-temperature fixability while ensuring durability, as the shell of core-shell toners tends to peel off, leading to image defects and contamination of image formation components.

Method used

A toner composition with a core particle coated by a shell containing a polyester resin and an amino resin, where the polyvalent metal content and shell thickness are optimized to enhance adhesion, resulting in a surface storage modulus that suppresses shell peeling and maintains developability over time.

Benefits of technology

The toner achieves both low-temperature fixability and long-term developability by preventing shell peeling, reducing cracking and contamination, and ensuring stable image quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599914000001
    Figure 0007599914000001
  • Figure 0007599914000002
    Figure 0007599914000002
  • Figure 0007599914000003
    Figure 0007599914000003
Patent Text Reader

Abstract

To provide a toner that prevents peeling off of a shell while maintaining and improving low temperature fixability to have excellent developability over a long period.SOLUTION: A toner has a toner particle that has a core particle having a resin component, a shell covering the surface of the core particle, and polyvalent metal. The resin component contains a polyester resin. The shell contains an amino resin. In an electron image of the cross section of the toner photographed by using a transmission electron microscope, on the interface between the core and the shell and in the vicinity of the interface, the content P (M) of the polyvalent metal obtained through energy dispersion type X-ray analysis is 0.0010 atomic% or more and 2.00 atomic% or less. In nano-indentation measurement of the toner, the surface storage modulus of the toner with a load of 30 μN at 25°C is 6.50 GPa or more and 12.00 GPa or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to toners used to form toner images by developing electrostatic latent images formed by methods such as electrophotography, electrostatic recording, and toner jet recording. [Background technology]

[0002] In recent years, methods for visualizing image information via electrostatic latent images, such as electrophotography, have been used in a variety of fields. In addition to higher image quality and faster speeds, there is a demand for smaller copiers and printers that are more energy efficient and have longer life. In particular, there is an increasing demand for reducing the running costs of copiers and printers. Therefore, there is a demand for toners that are excellent in energy saving and have a long life so that they can print for a long period of time with one cartridge. From the viewpoint of energy saving, binder resins with low melting points and glass transition points and release agents with low melting points are often used to prepare toners with excellent low-temperature fixing properties that enable reduction in power consumption during heat fixing. When such toners are stored at high temperatures, there is a problem that the toner particles tend to fuse together. To address the above-mentioned problems, for example, Patent Document 1 discloses a core-shell toner in which a thermosetting resin or a thermoplastic resin is used for the shell layer. However, a series of operations involved in the image formation process in which the electrostatic latent image is visualized by the toner all involve contact between toners or between the toner and a member, and the toner is repeatedly subjected to loads at each such contact, resulting in a problem that the toner deforms when exposed to heat or stress in this way, causing cracks or crushing of the toner. To address this problem, for example, Patent Document 2 proposes a toner whose displacement amount measured by nanoindentation method and surface hardness fall within a specific range. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-045844 A [Patent Document 2] JP 2014-164274 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, low-temperature fixability and development durability are mutually exclusive properties, and it has become clear that it is difficult to achieve both of these requirements for recent design concepts. From the viewpoint of a long-life development system, it has been found that the shell of the core-shell toner peels off from the core particle when repeated printing is continued using the above toner. If the shell peels off from the core particle, the charging property is disturbed, and the peeled shell and exposed core particles cause contamination and adhesion to components involved in image formation such as developing members and charging members, resulting in poor images. Therefore, there is still room for improvement in terms of durability. The present disclosure provides a toner that exhibits excellent developability over a long period of time by suppressing shell peeling while maintaining and improving low-temperature fixability. [Means for solving the problem]

[0005] The present disclosure provides a toner having core particles having a resin component, a shell covering the surface of the core particles, and toner particles having a polyvalent metal, The resin component contains a polyester resin, The shell comprises an amino resin; In an electron image of a cross section of the toner particle taken using a transmission electron microscope, a content P(M) of polyvalent metals obtained by performing a line scan in a range of 0.85d to 1.15d from the outer periphery of a cross section of a toner particle toward a center of the toner particle in a direction perpendicular to the surface of the toner particle, where d (nm) is the thickness of the shell, is 0.0010 atomic % or more and 2.0000 atomic % or less; The toner has a surface storage elastic modulus of 6.50 GPa or more and 12.00 GPa or less at 25° C. and a load of 30 μN, as measured by nanoindentation. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide a toner having excellent developability over a long period of time by suppressing shell peeling while maintaining and improving low-temperature fixability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] In the present disclosure, the expressions "XX or more and YY or less" and "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified. When numerical ranges are stated in stages, the upper and lower limits of each numerical range can be combined in any way.

[0008] The present disclosure provides a toner having core particles having a resin component, a shell covering the surface of the core particles, and toner particles having a polyvalent metal, The resin component contains a polyester resin, The shell comprises an amino resin; the average thickness of the shell is 1.0 nm or more and 30.0 nm or less; In an electron image of a cross section of the toner particle taken using a transmission electron microscope, a content P(M) of polyvalent metals obtained by performing a line scan in a range of 0.85d to 1.15d from the outer periphery of a cross section of a toner particle toward a center of the toner particle in a direction perpendicular to the surface of the toner particle, where d (nm) is the thickness of the shell, is 0.0010 atomic % or more and 2.0000 atomic % or less; The toner is characterized in that, in nanoindentation measurement of the toner, the toner has a surface storage modulus of 6.50 GPa or more and 12.00 GPa or less at 25° C. under a load of 30 μN.

[0009] In the toner, the polyvalent metal is present at the interface between the core particle and the shell and in the vicinity of the interface, and the adhesion between the core particle and the shell is high. Therefore, even if the storage modulus of the toner surface is high for a soft core particle having low temperature fixing property, the adhesion between the core particle and the shell is high, and shell peeling can be suppressed. In a long-life development system, the high demand for toner developability can be satisfied while maintaining low temperature fixing property. The present inventors believe that the reason why the toner has such an effect is as follows.

[0010] In order to satisfy the high demand for toner developability in a long-life development system, it is essential that the surface storage modulus of the toner is 6.50 GPa or more and 12.00 GPa or less at 25° C. and a load of 30 μN in nanoindentation measurement of the toner. The storage modulus of the toner surface represents the storage modulus of the extreme surface layer of the toner, and the inventors have found that there is a correlation with development durability through their investigation.

[0011] As described above, the toner cracks and breaks when it is repeatedly subjected to stress from members such as the developing roller and the developing blade during development. In addition, inorganic or organic fine particles called external additives are externally added to the surface of the toner particles as necessary for the purpose of assisting charging and improving fluidity. By the surface storage modulus being 6.50 GPa or more, external stress Even if the additives are added repeatedly, the toner is less likely to crack or break. In addition, the additives work effectively for a long period of time, resulting in a toner with excellent development durability. In addition, by having the surface storage elastic modulus of 12.00 GPa or less, the external additives are appropriately fixed, the toner is less likely to deform, and the external additives effectively work for a long period of time, resulting in a toner having excellent development durability that can suppress image defects such as fog and development streaks.

[0012] Furthermore, the surface storage elastic modulus is preferably in the range of 6.80 GPa to 11.60 GPa, inclusive, which provides a toner having superior development durability. The surface storage modulus under a load of 30 μN can be controlled by the glass transition temperature Tg and acid value of the resin on the toner surface, and the amount of metal ions at and near the interface between the core particle and the shell.

[0013] To meet the above-mentioned desires for toner developability, the shell contains an amino resin. Examples of the amino resin include a melamine resin, a guanamine resin, an aniline resin, a urea resin, a polyurethane resin, a sulfonamide resin, a polyimide resin, and derivatives of these resins. The amino resin is preferably a thermosetting resin.

[0014] Suitable examples of thermosetting monomers that can be used in the amino resin include methylolmelamine, hexamethylolmelamine, melamine, methylolated urea (more specifically, dimethyloldihydroxyethyleneurea, etc.), urea, benzoguanamine, acetoguanamine, and spiroguanamine. More preferably, it is at least one selected from the group consisting of melamine resin, urea resin, guanamine resin and aniline resin, and even more preferably, it is a melamine resin. The melamine resin is preferably a methylol melamine resin, a hexamethylol melamine resin, or a methoxymethylol melamine resin, and more preferably a hexamethylol melamine resin.

[0015] Thermosetting resins are obtained by crosslinking one or more thermosetting monomers. A thermosetting monomer is a monomer that has crosslinking properties. For example, when the same type of monomer is three-dimensionally linked to each other via "-CH2-" to form a thermosetting resin, the monomer corresponds to a thermosetting monomer. Thermosetting resins have excellent heat resistance and are difficult to deform, so it is believed that using a thermosetting resin for the shell makes the toner less likely to deform even when external stress is applied, thereby suppressing image defects such as fog and development streaks. In particular, melamine resin is a polycondensation product of melamine in which three amino groups are bonded to a triazine skeleton, and is therefore thought to form a stronger three-dimensional network structure.

[0016] In nanoindentation measurement of the toner, the surface storage modulus of the toner at 25° C. under a load of 50 μN is preferably 0.20 GPa or more and 12.00 GPa or less, and more preferably 0.30 GPa or more and 11.80 GPa or less. Nanoindentation measurement at a load of 50 μN measures the viscoelasticity closer to the core of the toner particle than measurement at a load of 30 μN. When the surface storage modulus of the toner particles at 50 μN falls within the above range, the toner has high development durability and excellent low-temperature fixing properties with little fixing inhibition. The surface storage modulus at a load of 50 μN can be controlled by the Tg, acid value, and metal ion amount of the resin of the core particle.

[0017] The average shell thickness is preferably 1.0 nm or more and 30.0 nm or less. In the fixing process of the toner, heat and pressure are applied from a member such as a fixing roller, and the toner is fixed onto the paper. By making the shell thickness 30.0 nm or less, the toner has excellent low-temperature fixing properties. The repeated stress that the toner receives during development causes the toner to crack or break apart. By making the shell thickness 1.0 nm or more, the toner is prevented from deteriorating. It is more preferable that the average shell thickness is 1.1 nm or more and 29.0 nm or less. The shell does not necessarily need to cover the entire surface of the core particle, and the core particle may have a portion that is partially exposed.

[0018] In order to achieve both low-temperature fixing property and high development durability in a toner having low-temperature fixing property, it is important to improve the adhesion between the core particle and the shell, and for this purpose, a polyvalent metal is required. In an electron image of a cross section of a toner particle taken using a transmission electron microscope, the polyvalent metal content P(M) obtained by line scanning from the outer periphery of the cross section of the toner particle toward the center of the toner particle in a direction perpendicular to the surface of the toner particle in a range of 0.85d to 1.15d using energy dispersive X-ray analysis, where d (nm) is the shell thickness, must be 0.0010 atomic % or more and 2.0000 atomic % or less. When the thickness of the shell is d (nm), the range of 0.85d to 1.15d from the outer periphery of the cross section of the toner particle toward the center of the toner particle in a direction perpendicular to the surface of the toner particle indicates the interface and the vicinity of the interface between the core particle and the shell. It is believed that toner particles that satisfy the above conditions have the shell and core particles fixed by non-covalent bonds with the polyvalent metal. By having P(M) of 0.0010 atomic % or more, the core particle and shell are sufficiently adhered to each other, and peeling of the shell due to external forces can be suppressed.

[0019] In addition, by making P(M) 2.0000 atomic % or less, the toner has a certain viscosity due to moderate adhesion, dissipates impact force, and is less likely to break. Preferably, P(M) is 0.0012 atomic % or more and 1.9400 atomic % or less. P(M) can be controlled by the amount of polyvalent metal ions added.

[0020] Moreover, the polyvalent metal is preferably at least one selected from the group consisting of Al, Ca, and Mg. Of these metals, one may be used alone, or a plurality of types may be used in combination. These metals are divalent or higher metals, and strengthen the crosslinking between the core and the shell. More preferably, it is at least one selected from the group consisting of Ca and Al, which have a small ionic radius, and even more preferably it is Al, which is a trivalent metal. Ca and Al, which have a small ionic radius, strongly attract the cross-linking sites between the core and shell, resulting in stronger cross-linking and a toner with high adhesion. Furthermore, because they are trivalent metals, the number of cross-linking points between the core and shell increases, resulting in stronger cross-linking and a toner with high adhesion.

[0021] The polyvalent metal is preferably Mg derived from magnesium hydroxide, Mg derived from magnesium chloride, or Al derived from aluminum sulfate. Such metal salts can be added as flocculants in an emulsion aggregation method, added to an aqueous medium in a dissolution suspension method, or added to an aqueous medium in which core particles are dispersed, to allow the desired polyvalent metal to be contained at or near the interface between the core particle and the shell.

[0022] It is essential for the resin component of the core particles to contain a polyester resin in order to improve the adhesion with the shell resin by the above-mentioned interaction. The polyester resin is preferably a polycondensate of an alcohol component and a carboxylic acid component. By using polyester resin as the resin component of the core particles, the polyester resin is oriented on the outermost surface. When a water-soluble metal salt with a valence of 2 or more is added to the outermost surface of the core particles, the water-soluble metal salt dissolves in the aqueous medium and becomes a metal ion with a valence of 2 or more.

[0023] Polyester resin contains carboxyl groups. It is believed that these divalent or higher metal ions coordinate to the carboxyl groups of the polyester resin. When amino resin is used for the shell, the metal ions coordinated to the carboxyl groups of the polyester resin form non-covalent bonds with the nitrogen element, resulting in intermolecular The interaction makes it possible to improve the adhesion between the core particle and the shell. This improvement in adhesion makes it possible to suppress shell peeling even during long-term use, and by suppressing shell peeling, a toner with excellent durability can be obtained in which development problems such as fog and streaks are suppressed over a long period of time.

[0024] The resin component of the core particle preferably contains a polyester resin in an amount of 50.0% by mass or more in the resin component. When the polyester resin is 50.0% by mass or more in the resin component of the core, the adhesion between the core and the shell is improved, and peeling of the shell is suppressed even during long-term use. It is more preferably 55.0% by mass or more, and further preferably 60.0% by mass or more. There is no particular upper limit, but it is preferably 98.0% by mass or less, and more preferably 95.0% by mass or less.

[0025] Examples of the resin component of the core particles that can be used include polyester resin, polycarbonate resin, phenol resin, epoxy resin, polyamide resin, cellulose resin, and styrene-acrylic resin.

[0026] Examples of the alcohol component include ethylene glycol, propylene glycol, 1, Examples of such bisphenol A include 3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, cyclohexanedimethanol, butenediol, octene diol, cyclohexene dimethanol, hydrogenated bisphenol A, an ethylene oxide adduct of bisphenol A, and a propylene oxide adduct of bisphenol A.

[0027] Examples of polyvalent carboxylic acids include aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid, or anhydrides thereof; alkyl dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, or anhydrides thereof; succinic acid or anhydrides thereof substituted with an alkyl or alkenyl group having 6 to 18 carbon atoms; and unsaturated dicarboxylic acids such as fumaric acid, maleic acid, and citraconic acid, or anhydrides thereof.

[0028] [Resin component of core particles] The resin component of the core particles may contain other resins in combination as long as it contains a polyester resin. Examples of the resin include the following: homopolymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-α-methyl chloromethacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; polyvinyl chloride, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins.

[0029] The resin component of the core particle preferably contains a styrene-acrylic resin in addition to a polyester resin. The content of the styrene-acrylic resin in the resin component is preferably 2.0% by mass or more and 50.0% by mass or less, more preferably 5.0% by mass or more and 45.0% by mass or less.

[0030] The acid value of the polyester resin is preferably 1 mgKOH / g or more and 50 mgKOH / g or less from the viewpoint of the stability of the triboelectric charge. The acid value can be adjusted to the above range by adjusting the type and amount of monomer used in the resin. Specifically, the acid value can be controlled by adjusting the alcohol monomer component ratio / acid monomer component ratio and molecular weight during the production of the resin. Furthermore, a crystalline polyester resin can also be used as the resin component of the core particles.

[0031] [Coloring agent] The toner may contain a colorant. The colorants include the following: Examples of black colorants include carbon black, and a mixture of a yellow colorant, a magenta colorant, and a cyan colorant toned to black. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of the image quality of a full-color image. Magenta colored pigments include: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35. Magenta coloring dyes include: CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1, and other solvent dyes; CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28, and other basic dyes.

[0032] Cyan coloring pigments include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. Cyan coloring dyes include CI Solvent Blue 70. Yellow coloring pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow coloring dyes include CI Solvent Yellow 162. The amount of the colorant used is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin.

[0033] [wax] The toner preferably contains a wax. Examples of the wax include the following. Low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymer, microcrylonitrile Hydrocarbon waxes such as stalin wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or their block copolymers; waxes whose main component is fatty acid esters such as carnauba wax; partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax. Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene Saturated fatty acid bisamides such as bisstearamide; unsaturated fatty acid amides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N' dioleyl adipamide, and N,N' dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearamide and N,N' distearyl isophthalamide; fatty acid metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols, such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.

[0034] Among these waxes, from the viewpoint of improving low-temperature fixability, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax are preferred. The content of the wax is preferably 0.5 parts by mass or more and 25.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin. From the viewpoint of achieving both storage stability and high-temperature offset resistance of the toner, it is preferable that the peak temperature of the maximum endothermic peak of the wax existing in the temperature range of 30°C or more and 200°C or less in the endothermic curve during temperature rise measured by a differential scanning calorimeter (DSC) is 50°C or more and 110°C or less.

[0035] [Charge control agent] The toner may contain a charge control agent as necessary. Any known charge control agent may be used, but a metal compound of an aromatic carboxylic acid is particularly preferred, as it is colorless, can charge the toner quickly, and can stably maintain a constant charge amount. Examples of negative charge control agents include the following: metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes. The charge control agent may be added internally or externally to the toner particles. The amount of the charge control agent added is preferably 0.2 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin.

[0036] The toner may be mixed with a magnetic carrier and used as a two-component developer, since this allows stable images to be obtained over a long period of time. As the magnetic carrier, the following known materials can be used: iron powder with an oxidized surface, or unoxidized iron powder, iron, lithium, calcium, magnesium, nickel, copper, zinc, etc. Metal particles such as lead, cobalt, manganese, chromium, and rare earth elements, alloy particles, oxide particles, and magnetic materials such as ferrite, as well as magnetic material-dispersed resin carriers (so-called resin carriers) that contain magnetic materials and a binder resin that holds the magnetic materials in a dispersed state.

[0037] The toner particles may be produced by any method. For example, a method of producing a toner directly in a hydrophilic medium, such as an emulsion aggregation method, a dissolution suspension method, or a suspension polymerization method, may be used. A pulverization method may also be used, and the toner obtained by the pulverization method may be thermally spheronized. Among them, toners manufactured by the emulsion aggregation method are more likely to achieve the above effects. The reason is that the polyester resin is likely to come out to the surface of the toner particles during the manufacturing process. In the emulsion aggregation method, in which aggregated particles are fused to form core particles, the carboxyl groups of the polyester resin, which serve as the bonding sites with the shell, are likely to come out to the surface, and the adhesion between the core and shell is stronger. A method for producing toner particles by the emulsion aggregation method will be exemplified below.

[0038] (Dispersion liquid preparation process) The preparation of a dispersion of resin particles for producing resin particles as core particles will now be described. The dispersion of resin particles is prepared, for example, as follows. When the resin in the resin particles is a homopolymer or copolymer of a vinyl monomer (vinyl resin), the vinyl monomer is subjected to emulsion polymerization or seed polymerization in an ionic surfactant to prepare a dispersion in which resin particles of a homopolymer or copolymer of a vinyl monomer (vinyl resin) are dispersed in the ionic surfactant. When the resin in the resin particles is a resin other than a vinyl resin such as a polyester resin, the resin is mixed with an aqueous medium in which an ionic surfactant or a polymer electrolyte is dissolved.

[0039] Thereafter, the solution is heated to a temperature above the melting point or softening point to dissolve the resin particles, and a dispersion liquid in which the resin particles are dispersed in the ionic surfactant is prepared using a dispersing machine with strong shear force such as a homogenizer. The means for dispersion is not particularly limited, and examples thereof include known dispersion devices such as a rotary shear homogenizer, a ball mill having media, a sand mill, and a dyno mill.

[0040] A phase inversion emulsification method may also be used as a method for preparing the dispersion liquid. In the phase inversion emulsification method, a binder resin is dissolved in an organic solvent, a neutralizer and a dispersion stabilizer are added as necessary, and an aqueous solvent is dropped under stirring to obtain emulsified particles, and then the organic solvent in the resin dispersion liquid is removed to obtain an emulsion liquid. In this case, the order of adding the neutralizer and the dispersion stabilizer may be changed. The number-average particle diameter of the resin particles is usually 1 μm or less, and preferably 0.01 to 1.00 μm. When the number-average particle diameter is within the above range, the particle size distribution of the toner can be made sharp, and the generation of free particles can be suppressed. In addition, uneven distribution of the resin particles among the toner particles is reduced, the dispersion of each component in the toner is improved, and the variation in performance and reliability is reduced.

[0041] If necessary, the colorant particle dispersion is adjusted. The colorant particle dispersion is prepared by dispersing at least colorant particles in a dispersant. The number-average particle diameter of the colorant particles is preferably 0.5 μm or less, more preferably 0.2 μm or less. When the number-average particle diameter is 0.5 μm or less, diffuse reflection of visible light can be prevented, and coloring power, color reproducibility, and OHP transmittance are improved. In addition, uneven distribution of the colorant between toner particles is reduced, colorant dispersion in the toner is improved, and variations in performance and reliability are reduced.

[0042] If necessary, a wax particle dispersion is prepared. The wax particle dispersion is prepared by dispersing at least wax particles in a dispersant. The number average particle diameter of the wax particles is When the number-average particle diameter is within the above range, uneven distribution of the wax among the toner particles is reduced, the dispersion of the wax in the toner particles is improved, and the variation in performance and reliability is reduced.

[0043] The combination of colorant particles, resin particles, and wax particles is not particularly limited and can be freely selected depending on the purpose. In addition to the resin particle dispersion, colorant particle dispersion, and wax particle dispersion, a particle dispersion obtained by dispersing appropriately selected particles in a dispersant may be further mixed. The particles contained in the particle dispersion liquid are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include internal additive particles, charge control agent particles, inorganic particles, abrasive particles, etc. These particles may be dispersed in a resin particle dispersion liquid or a colorant particle dispersion liquid.

[0044] Examples of dispersants contained in the resin particle dispersion, colorant particle dispersion, wax fine dispersion, particle dispersion, and the like include aqueous media containing polar surfactants. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, and alcohols. These may be used alone or in combination of two or more. The content of the polar surfactant cannot be generally specified, and can be appropriately selected according to the purpose.

[0045] Examples of polar surfactants include anionic surfactants such as sulfate salts, sulfonate salts, phosphate salts, and soap salts; and cationic surfactants such as amine salts and quaternary ammonium salts. Specific examples of anionic surfactants include sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium alkylnaphthalenesulfonate, and sodium dialkylsulfosuccinate. Specific examples of cationic surfactants include alkylbenzene dimethyl ammonium chloride, alkyl trimethyl ammonium chloride, distearyl ammonium chloride, etc. These may be used alone or in combination of two or more.

[0046] In addition, these polar surfactants can be used in combination with non-polar surfactants, such as polyethylene glycol-based, alkylphenol ethylene oxide adduct-based, polyhydric alcohol-based, and other non-ionic surfactants. The content of the colorant particles is preferably 0.1 parts by mass to 30 parts by mass with respect to 100 parts by mass of the resin component in the aggregated particle dispersion when the aggregated particles are formed. The content of the wax particles is preferably 0.5 to 25 parts by mass, and more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the resin component in the aggregated particle dispersion when the aggregated particles are formed.

[0047] Furthermore, in order to more precisely control the chargeability of the resulting toner, charge control particles and resin particles may be added after the aggregated particles are formed. The particle size of resin particles, colorant particle dispersions, wax fine dispersions, particle dispersions, etc. is measured using a laser diffraction / scattering type particle size distribution measuring device LA-920 manufactured by Horiba, Ltd.

[0048] (Agglutination process) The aggregation process for forming aggregated particles is a process for forming aggregated particles containing resin particles, colorant particles, wax particles, etc. in an aqueous medium containing at least resin particles, and, if necessary, colorant particles, wax particles, etc. The aggregated particles can be formed in an aqueous medium by, for example, adding a pH adjuster, an aggregate agent, and a stabilizer to the aqueous medium and mixing the mixture, and then appropriately applying temperature, mechanical power, and the like. Examples of pH adjusters include alkalis such as ammonia and sodium hydroxide, and acids such as nitric acid and citric acid. Examples of flocculants include monovalent metal salts such as sodium and potassium, divalent metal salts such as calcium and magnesium, trivalent metal salts such as iron and aluminum, and alcohols such as methanol, ethanol, and propanol.

[0049] The stabilizer mainly includes a polar surfactant itself or an aqueous medium containing the same, etc. For example, when the polar surfactant contained in each particle dispersion is anionic, a cationic stabilizer can be selected. The addition and mixing of the flocculant and the like is preferably carried out at a temperature equal to or lower than the glass transition temperature of the resin contained in the aqueous medium. When mixing is carried out under this temperature condition, the flocculation proceeds in a stable state. Mixing can be carried out using, for example, a known mixing device, homogenizer, mixer, etc.

[0050] In addition, in the aggregation process, it is also possible to obtain aggregated particles having a core / shell structure in which a shell is formed on the surface of a core aggregated particle by adhering a second resin particle to the surface of the aggregated particle using a resin particle dispersion liquid containing the second resin particle and forming a coating layer (shell). The second resin particles used in this case may be the same as or different from the resin particles constituting the core aggregated particles. The aggregation step may be repeated in stages a number of times.

[0051] (fusion process) The fusion process is a process in which the obtained aggregated particles are heated and fused. Prior to the fusion process, a pH adjuster, a polar surfactant, a non-polar surfactant, etc. may be appropriately added to prevent fusion between toner particles. The heating temperature may be at least the glass transition temperature of the resin contained in the aggregated particles (if there are two or more types of resin, the glass transition temperature of the resin with the highest glass transition temperature) and less than the decomposition temperature of the resin. Therefore, the heating temperature differs depending on the type of resin in the binder resin particles and cannot be generally specified, but is generally at least the glass transition temperature of the resin contained in the aggregated particles and less than 140°C. Heating can be performed using a known heating device or tool.

[0052] The fusion time is short if the heating temperature is high, and long if the heating temperature is low. In other words, the fusion time depends on the heating temperature and cannot be specified in general, but it is generally 30 minutes to 10 hours. The toner particles obtained through the above steps can be separated into solid and liquid in accordance with a known method, and the toner particles can be recovered, and then washed, dried, etc. under appropriate conditions.

[0053] (External addition process) The toner particles may be used as they are as a toner. For the purpose of imparting various properties to the toner, an external additive may be attached to the surface of the toner particles. The toner preferably contains toner particles and an external additive. From the viewpoint of durability when added to toner particles, the external additive preferably has a particle size of 1 / 10 or less of the average particle size of the toner particles before the external additive is added. Examples of the external additive include the following. Metal oxides such as aluminum oxide, titanium oxide, strontium titanate, cerium oxide, magnesium oxide, chromium oxide, tin oxide, and zinc oxide; nitrides such as silicon nitride; carbides such as silicon carbide; inorganic metal salts such as calcium sulfate, barium sulfate, and calcium carbonate; fatty acid metal salts such as zinc stearate and calcium stearate; carbon black, and silica. Of these, silica is preferred.

[0054] The content of the external additive is preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.05 parts by mass or more and 5 parts by mass or less, based on 100 parts by mass of the toner particles. One type of external additive may be used alone, or multiple types may be used in combination. From the viewpoint of charging stability, it is preferable to use these external additives whose surfaces have been subjected to hydrophobic treatment. Examples of the hydrophobic treatment agent include silane coupling agents such as methyltrimethoxysilane, methyltriethoxysilane, isobutyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, and hexamethylenedisilazane.

[0055] The methods for measuring various physical properties will be described below. <Measurement of toner surface viscoelasticity> The surface storage modulus of the toner is measured by the nanoindentation method using a TI-950 System Triboindenter (manufactured by Hysitron Corporation) as a measuring device. The measurement sample was prepared by attaching toner to the tip of a Johnson & Johnson cotton swab in an environment of 25° C. and scattering 0.1 mg of toner on a 1 cm×1 cm silicon wafer. The sample is mounted on a sample stage, and measurement is started under nanoindentation conditions at room temperature (25° C.) using a Berkovich-type diamond indenter (TI-0039: angle 142.3°) (manufactured by Hysitron). In this case, it is important to set the focus of the measurement sample before starting the measurement and to perform the measurement under uniform focus conditions. The measurement sample is focused using a microscope on the software. The objective lens is adjusted from 5x to 20x to 50x in sequence. After this, the 50x objective lens is used for adjustment.

[0056] Next, the measurement space and load force are calibrated using a dedicated Al plate, and the position between the tip of the indenter and the focus position of the microscope camera is adjusted to align the Z axis of the indenter. Thereafter, the tip of the indenter is moved onto the silicon wafer to which the toner is attached, and the microscope is focused on the toner to be measured. After these calibrations are performed, measurements are performed under the following conditions: The load condition of the indenter is 30μN, and the load is applied from 0μN to 30μN at 0.5μN / s. After that, vibration is applied in the following order of frequency and time: 3.0Hz for 3 seconds, 30Hz for 5 seconds, 150Hz for 15 seconds, and 301.5Hz for 40 seconds, and the nano viscoelasticity is measured. At this time, a stabilization time of 1 second is given between each frequency change. The data at that time The number of plots is 200 at 100 pts / sec, and the average value is calculated. Start the measurement, and measure the frequency (Hz) on the horizontal axis and the storage modulus (GPa) and loss modulus ( The pressure is calculated as GPa. The above measurement is carried out for 30 toner particles, and the average value is adopted. In addition, the indenter is always cleaned (XY axis alignment of the indenter) for each particle before measurement. For the load condition of 50 μN, measurements were performed in the same manner as for the load condition of 30 μN, except that the load was increased from 0 μN to 50 μN at 0.5 μN / s.

[0057] (Isolation of toner particles from a toner) When toner particles are used as a sample, toner particles obtained by removing external additives from the toner by the following method can also be used. (1) Place 5 g of toner containing external additives in a sample bottle and add 200 mL of methanol. If necessary, add a few drops of a surfactant. As a surfactant, "Contaminon N" (a 10% aqueous solution of a nonionic surfactant, anionic surfactant, and organic builder, a pH 7 neutral detergent for cleaning precision measuring instruments, manufactured by Wako Pure Chemical Industries, Ltd.) can be used. (2) Disperse the sample in an ultrasonic cleaner for 5 minutes to separate the external additives. (3) The toner particles and the external additives are separated by suction filtration (10 μm membrane filter). (4) The above steps (2) and (3) are repeated three times. By the above-mentioned operation, toner particles from which the external additives have been removed can be obtained.

[0058] <Metal content measurement on cross section of toner particles> The content of polyvalent metals is measured from an electron image of a cross section of a toner particle using a transmission electron microscope (TEM) by the following method. The measurement sample is prepared by mixing a visible light curable embedding resin (D-800, manufactured by Nissin EM Co., Ltd.) with toner particles, and pressurizing and molding the mixture into a disk shape with a diameter of 7.9 mm and a thickness of 1.0±0.3 mm using a tablet molding machine in an environment of 25°C, and using a sample in which the toner particles are embedded. The pressure molding conditions are 35 MPa and 60 seconds. From this sample, a diamond-blade-equipped ultramicrotome (EM UC7: manufactured by Leica Co., Ltd.) is used to cut a film thickness of 10 mm at a cutting speed of 0.6 mm / s. Cut out a 100 nm thin sample. This sample is magnified 500,000 times using a transmission electron microscope (TEM) (JEM2800 type: manufactured by JEOL Ltd.) under conditions of an acceleration voltage of 200 keV and an electron beam probe size of 1 mm, and the cross section of the toner particle is observed. The cross section to be observed is to have a major axis of ±10% of the weight average particle diameter (D4) of the toner particle to be observed. Next, the spectrum of the constituent elements of the cross section of the obtained toner particle is collected using an energy dispersive X-ray scattering method (EDS: NSS Thermo electron). The range of spectrum collection is the range R in the following equation (1). A line scan is performed from the outer periphery of the cross section of a toner particle with a shell thickness of d (nm) toward the center of the toner particle in a direction perpendicular to the toner particle surface, and a spectrum of the polyvalent metal P (M) is collected. The shell thickness d in this measurement is measured in the same manner as in "Measurement of the average shell thickness" below. The average shell thickness of the four points on the toner particle to be measured is defined as d (nm). The shell and the core particles are distinguished by staining with osmium tetroxide, which selectively stains only the shell in the toner particles. Formula (1) 0.85d≦R≦1.15d From the spectrum obtained, quantitative analysis is performed by the Cliff-Lorimer method at the maximum value of the polyvalent metal peak value P(M) in the range of formula (1), and the polyvalent metal content P(M) atomic% is calculated. P(M) atomic% is the atomic weight fraction when all elements detected during analysis are taken as 100%. The Cliff-Lorimer method uses energy dispersive X-ray dispersive spectroscopy (EDS: NSS Thermo electron). The analysis conditions are qualitative sensitivity 5, overvoltage 1.5 keV, and the number of oxygen atoms 0. Matrix correction is performed to correct for the effects of coexisting elements, and calculations are performed. The above measurement is carried out on the cross sections of 20 toner particles, and the arithmetic average value is adopted.

[0059] <Measuring the average shell thickness> The measurement sample is prepared by mixing a visible light curable embedding resin (D-800, manufactured by Nissin EM Co., Ltd.) with toner, and pressurizing the mixture into a disk shape with a diameter of 7.9 mm and a thickness of 1.0±0.3 mm using a tablet press at 25°C. The pressurization conditions are 35 MPa and 60 seconds. The sample was then cut using a diamond blade ultramicrotome (EM UC7:L Using a cutting tool (manufactured by Eica), a thin sample with a film thickness of 100 nm is cut out at a cutting speed of 0.6 mm / s. The obtained sample is stained with osmium tetroxide. This operation selectively stains only the shell in the toner particle. Next, the cross section of the obtained thin sample was examined using a transmission electron microscope (TEM) (JEM2800 type: manufactured by JEOL Ltd.) under conditions of an accelerating voltage of 200 keV and an electron beam probe size of 1 mm. The TEM images are then analyzed using image analysis software to measure the shell thickness. Specifically, two perpendicular lines are drawn at approximately the center of the cross section of a toner particle, and the shell thickness is measured at each of the four points where the two lines intersect with the shell. The arithmetic average of the thicknesses measured at the four points is regarded as the shell thickness of the toner particle. The shell thickness is then measured for each of 20 toner particles, and the number-average value of the measured thicknesses is regarded as the evaluation value of the toner being measured (average shell thickness).

[0060] <Method of measuring weight average particle size (D4) of toner particles> The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data. The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels, and the measurement data is analyzed and calculated. The aqueous electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1 mass %, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before carrying out the measurements and analyses, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) Screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter, Inc.). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1,600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.

[0061] The specific measurement method is as follows. (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) Approximately 30 mL of the aqueous electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and approximately 0.3 mL of the diluent described below is added as a dispersant. Dilution solution: "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion-exchanged water. (3) A specified amount of ion-exchanged water is placed in the water tank of the ultrasonic disperser described below, which has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of the Conaminon N is added to this water tank. Ultrasonic disperser: "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 15°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner has been dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).

[0062] <Method for measuring the acid value of resin> The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of a resin is measured in accordance with JIS K 0070-1992, and specifically, it is measured according to the following procedure. (1) Preparation of reagents Dissolve 1.0 g of phenolphthalein in 90 ml of ethyl alcohol (95% by volume) and add ion-exchanged water to make 100 ml to obtain a phenolphthalein solution. Dissolve 7 g of special grade potassium hydroxide in 5 ml of water, and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, then filter to obtain a potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is determined by placing 25 ml of 0.1 mol / l hydrochloric acid in an Erlenmeyer flask, adding several drops of the phenolphthalein solution, and titrating with the potassium hydroxide solution, from the amount of the potassium hydroxide solution required for neutralization. The 0.1 mol / l hydrochloric acid used is prepared in accordance with JIS K 8001-1998. (2) Operation (A) Main Test Weigh out 2.0 g of sample into a 200 ml Erlenmeyer flask, add 100 ml of a toluene / ethanol (2:1) mixed solution, and dissolve for 5 hours. Next, add a few drops of the phenolphthalein solution as an indicator, and titrate with the potassium hydroxide solution. The end point of the titration is when the indicator remains a light red color for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (2:1) mixed solution is used). (3) The obtained result is substituted into the following formula to calculate the acid value. A = [(CB) × f × 5.61] / S Here, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added for the blank test (ml), C is the amount of potassium hydroxide solution added for the main test (ml), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).

[0063] <Measurement of resin glass transition temperature (Tg)> The Tg of a resin is measured using a differential scanning calorimeter (DSC measuring device). The differential scanning calorimeter uses a differential scanning calorimeter analyzer "Q1000" (product name, manufactured by TA Instruments) and performs measurements in accordance with ASTM D3418-82 as follows. 3 mg of the measurement sample (resin) is precisely weighed out. This is placed in an aluminum pan, and an empty aluminum pan is used as a control. After maintaining equilibrium at 20°C for 5 minutes, measurements are performed in the measurement range of 20°C to 180°C at a heating rate of 10°C / min. The glass transition temperature is determined by the midpoint method. EXAMPLES

[0064] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples. In the examples and comparative examples, the parts and percentages are all based on mass unless otherwise specified.

[0065] <Production of Polyester Resin 1 for Core Particles> In a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, the amounts of monomers shown in Table 1 were placed, and then 1.5 parts of dibutyltin were added as a catalyst per 100 parts of the total amount of monomers. Next, the temperature was quickly raised to 180°C under normal pressure in a nitrogen atmosphere, and then water was distilled off while heating from 180°C to 210°C at a rate of 10°C / hour to carry out polycondensation. Thereafter, the temperature was raised to 210° C., and the reaction was continued while reducing the pressure until a desired molecular weight was reached, thereby obtaining a polyester resin 1.

[0066] <Production of Polyester Resins 2 to 5 for Core Particles> Polyester resins 2 to 5 were prepared in the same manner as for polyester resin 1, except that the raw materials were changed as shown in Table 1. The unit of Tg is °C. The abbreviations in the table are as follows. TPA: Terephthalic acid IPA: Isophthalic acid TMA: Trimellitic acid BPA-PO: Bisphenol A propylene oxide 2 mol adduct BPA-EO: Bisphenol A with 2 mol of ethylene oxide

[0067] [Table 1]

[0068] <Production of styrene-acrylic resin for core particles> Into a reaction vessel equipped with a stirrer, a thermometer, and a nitrogen inlet tube, 80.0 parts of styrene, 20.0 parts of n-butyl acrylate, and 0.3 parts of hexanediol diacrylate were added and heated to a temperature of 80° C. with stirring. Subsequently, 2.0 parts of Perbutyl O (10-hour half-life temperature 72.1° C. (manufactured by NOF Corp.)) was added as a polymerization initiator, and polymerization was continued for 5 hours to obtain a styrene-acrylic resin for core particles.

[0069] <Production of shell dispersion 1> In a 1 L three-neck flask equipped with a thermometer and a stirring blade, 300 parts of ion-exchanged water and dilute hydrochloric acid were added to adjust the pH to 4, and the mixture was kept at 30° C. The monomers in the amounts shown in Table 2 were added to this pH 4 adjusted solution and dispersed to obtain shell dispersion liquid 1.

[0070] <Production Examples of Shell Dispersions 2 to 5> Shell dispersions 2 to 5 were obtained in the same manner as in the production example of shell dispersion 1, except that the monomer composition was changed as shown in Table 2.

[0071] [Table 2]

[0072] (Preparation of Polyester Resin Particle Dispersion) 1,200 parts polyester resin -Ion-exchanged water 500 parts The above materials were placed in a stainless steel container, heated to 95°C in a hot bath, and melted. While thoroughly stirring at 7,800 rpm using a homogenizer (IKA Ultra Turrax T50), 0.1 mol / L sodium bicarbonate was added to adjust the pH to greater than 7.0. Thereafter, a mixed solution of 3 parts of sodium dodecylbenzenesulfonate and 297 parts of ion-exchanged water was gradually added dropwise to emulsify and disperse the mixture, thereby obtaining a polyester resin particle dispersion. The particle size distribution of this polyester resin particle dispersion 1 was measured using a particle size measuring device (LA-920, manufactured by Horiba, Ltd.), and the number-average particle size of the polyester resin particle dispersion contained therein was 0.25 μm, and no coarse particles exceeding 1 μm were observed.

[0073] (Preparation of Styrene Acrylic Resin Particle Dispersion) 300 parts of xylene (boiling point 144° C.) was placed in a flask capable of being pressurized and decompressed, and the inside of the vessel was thoroughly replaced with nitrogen while stirring, and then the temperature was raised to reflux. Under this reflux, Styrene 88.50 parts Methyl methacrylate 2.50 parts 2-Hydroxyethyl methacrylate 5.00 parts Methacrylic acid 4.00 parts Di-tert-butyl peroxide 2.00 parts After adding the mixed solution, polymerization was carried out for 5 hours at a polymerization temperature of 175° C. and a pressure during reaction of 0.100 MPa. Thereafter, a desolvation step was carried out under reduced pressure for 3 hours to remove xylene, and pulverization was carried out to obtain styrene acrylic resin 1. Using styrene-acrylic resin 1 instead of polyester resin 1, a styrene-acrylic resin particle dispersion was obtained in the same manner as in (Preparation of polyester resin particle dispersion).

[0074] (Preparation of Wax Particle Dispersion) -Ion-exchanged water 500 parts Wax (hydrocarbon wax; maximum endothermic peak temperature 77°C) 250 parts The above materials were placed in a stainless steel container, heated to 95°C in a hot bath, and melted. While thoroughly stirring at 7,800 rpm using a homogenizer (IKA Ultra Turrax T50), 0.1 mol / L sodium bicarbonate was added to adjust the pH to greater than 7.0. Thereafter, a mixed solution of 5 parts of sodium dodecylbenzenesulfonate and 245 parts of ion-exchanged water was gradually added dropwise to emulsify and disperse the wax particles. The particle size distribution of the wax particles contained in this wax particle dispersion was measured using a particle size measuring device (LA-920, manufactured by Horiba, Ltd.), and the number-average particle size of the wax particles contained was 0.35 μm, and no coarse particles exceeding 1 μm were observed.

[0075] (Preparation of Colorant Particle Dispersion 1) CI Pigment Blue 15:3 100 parts Sodium dodecylbenzenesulfonate 5 parts -Ion-exchanged water 400 parts The above was mixed and dispersed using a sand grinder mill. The particle size distribution of the colorant particles contained in this colorant particle dispersion was measured using a particle size measuring device (LA-920, manufactured by Horiba, Ltd.), and the number-average particle size of the colorant particles contained was 0.2 μm, and no coarse particles exceeding 1 μm were observed.

[0076] (Preparation of Colorant Particle Dispersion 2) CI Pigment Red 122 100 parts Sodium dodecylbenzenesulfonate 5 parts -Ion-exchanged water 400 parts The above was mixed and dispersed using a sand grinder mill. The particle size distribution of the colorant particles contained in this colorant particle dispersion was measured using a particle size measuring device (LA-920, manufactured by Horiba, Ltd.), and the number-average particle size of the colorant particles contained was 0.2 μm, and no coarse particles exceeding 1 μm were observed.

[0077] (Preparation of Colorant Particle Dispersion 3) CI Pigment Yellow 74 100 parts Sodium dodecylbenzenesulfonate 5 parts -Ion-exchanged water 400 parts The above was mixed and dispersed using a sand grinder mill. The particle size distribution of the colorant particles contained in this colorant particle dispersion was measured using a particle size measuring device (LA-920, manufactured by Horiba, Ltd.), and the number-average particle size of the colorant particles contained was 0.2 μm, and no coarse particles exceeding 1 μm were observed.

[0078] <Production of Toner 1> (Production of Core Particle 1) Polyester resin particle dispersion 450 parts Styrene acrylic resin particle dispersion 50 parts Colorant particle dispersion 1 50 parts Wax particle dispersion 50 parts Sodium dodecylbenzenesulfonate 5 parts A polyester resin particle dispersion, a styrene acrylic resin particle dispersion, a wax particle dispersion, and sodium dodecylbenzenesulfonate were charged into a reactor (1-liter flask, anchor blade with baffles) and mixed uniformly. Meanwhile, colorant particle dispersion 1 was mixed uniformly in a 500-mL beaker, and this was gradually added to the reactor while stirring to obtain a mixed dispersion. 0.5 parts of aluminum sulfate aqueous solution (solid content) was added dropwise while stirring the obtained mixed dispersion to form aggregated particles. After the dropwise addition was completed, the system was purged with nitrogen and the temperature was maintained at 50° C. for 1 hour and then at 55° C. for 1 hour. The temperature was then raised to 90°C and held for 30 minutes. The temperature was then lowered to 63°C and held for 3 hours to form fused particles. The reaction was carried out in a nitrogen atmosphere. After the specified time had elapsed, the temperature was lowered at a rate of 0.5°C per minute until the mixture reached room temperature. After cooling, the reaction product was subjected to solid-liquid separation under a pressure of 0.4 MPa in a 10 L pressure filter to obtain a toner cake. Thereafter, ion-exchanged water was added to the pressure filter until it was filled with water, and the filter was washed under a pressure of 0.4 MPa. The filter was washed in the same manner for a total of three times. The toner cake was dispersed in 1000 parts of a 50:50 mixed solvent of methanol / water in which 0.15 parts of a nonionic surfactant was dissolved, to obtain a surface-treated core particle dispersion. This core particle dispersion was poured into a pressure filter, and 5 L of ion-exchanged water was added thereto. After that, solid-liquid separation was performed under a pressure of 0.4 MPa, and fluidized bed drying was performed at 45° C. to obtain core particles 1.

[0079] (Production of toner particles 1) Shell dispersion 1 was added to the core particle 1 dispersion so that the resin solid content was 1.0 part per 100.0 parts of solid content. Sodium hydroxide solution was added while stirring at room temperature (about 25°C) and a rotation speed of 200 rpm to adjust the pH to 8.0. The mixture was then heated to 70°C and stirred for 2 hours to form a shell layer on the surface of the core particles. Next, the pH of the dispersion of toner particles was adjusted (neutralized) to 7 using hydrochloric acid, and the dispersion of toner particles was cooled to room temperature. After that, hydrochloric acid was added to dissolve calcium phosphate, which was a dispersant, and the mixture was filtered, washed with water, and dried to obtain toner particles 1 having a core-shell structure and a weight average particle size (D4) of 6.9 μm.

[0080] (Toner 1 Production) 100.0 parts of toner particles 1 and 1.5 parts of dry silica particles ("AEROSIL (registered trademark) REA90" manufactured by Nippon Aerosil Co., Ltd.: positively charged hydrophobically treated silica particles) were mixed for 3 minutes using an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.) to adhere the silica particles to the toner particles 1. The mixture was then sieved through a 300 mesh (opening 48 μm) to obtain toner 1. The physical properties of the obtained toner 1 are shown in Table 4.

[0081] <Production of Toners 2 to 19 and 22 to 29> Toners 2 to 19 and 22 to 29 were obtained by the same manufacturing method as for toner 1 except for the changes shown in Table 3. Note that the aluminum sulfate used as the coagulant was changed to calcium chloride in toner 14, to magnesium chloride in toner 15, and sodium chloride in toner 22. The physical properties are shown in Table 4.

[0082] <Production of Toner 20> (Production of Core Particles 20) Polyester resin 1 60.0 parts Styrene-acrylic resin for core particles: 40.0 parts CI Pigment Blue 15:3 (copper phthalocyanine) 5.0 parts Ester wax (behenyl behenate: melting point 72°C) 15.0 parts Fischer-Tropsch wax (Sasol C105, melting point: 105°C) 2.0 copies Methyl ethyl ketone 100.0 parts Ethyl acetate 100.0 parts The above materials were dispersed for 3 hours using an Attritor (manufactured by Mitsui Kinzoku Co., Ltd.) to obtain a colorant dispersion. On the other hand, 1.8 parts of magnesium hydroxide was added to 300.0 parts of ion-exchanged water heated to 60°C. The above-mentioned colorant dispersion was added to the above-mentioned aqueous medium, and the mixture was stirred at a stirring speed of 12,000 rpm for 15 minutes at 65°C under a N2 atmosphere using the TK homomixer to granulate colorant particles. Thereafter, the TK homomixer was changed to a conventional propeller stirrer, the stirring speed of the stirrer was maintained at 150 rpm, the internal temperature was raised to 95°C and held for 3 hours to remove the solvent from the dispersion, and a dispersion of core particles 20 was prepared.

[0083] (Production of toner particles 20) For 100.0 parts of the solid content of the above-mentioned core particle 20 dispersion, add 1 shell dispersion to the resin solid content The mixture was added so that the total amount of the core particles was 1.0 part. Then, an aqueous sodium hydroxide solution was added while stirring at room temperature (about 25°C) and a rotation speed of 200 rpm to adjust the pH to 8.0. The mixture was then heated to 70°C and stirred for 2 hours to form a shell layer on the surface of the core particles. Next, the pH of the dispersion of toner particles was adjusted (neutralized) to 7 using hydrochloric acid, and the dispersion of toner particles was cooled to room temperature. After that, hydrochloric acid was added to dissolve calcium phosphate, which was a dispersant, and the mixture was filtered, washed with water, and dried to obtain toner particles 20 having a core-shell structure and a weight average particle size (D4) of 6.9 μm.

[0084] (Manufacture of Toner 20) 100.0 parts of toner particles 20 and 1.5 parts of dry silica particles ("AEROSIL (registered trademark) REA90" manufactured by Nippon Aerosil Co., Ltd.: positively charged hydrophobically treated silica particles) were mixed for 3 minutes using an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.) to adhere the silica particles to the toner particles 20. The mixture was then sieved through a 300 mesh (opening 48 μm) to obtain toner 20. The above evaluations were carried out using toner 20, and the obtained physical properties are shown in Table 4.

[0085] <Production of Toner 21> (Production of Core Particles 21) Polyester resin 1: 60.0 parts Styrene-acrylic resin for core particles: 40.0 parts CI Pigment Blue 15:3 (copper phthalocyanine): 5.0 parts Ester wax (behenyl behenate: melting point 72°C) 15.0 parts Fischer-Tropsch wax (Sasol C105, melting point: 105°C): 2.0 copies The above materials were premixed in a Mitsui Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and then melt-kneaded using a twin-screw extruder (product name: PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) with the temperature set so that the molten temperature at the discharge outlet was 140°C. The obtained kneaded product was cooled, coarsely pulverized with a hammer mill, and then finely pulverized with a pulverizer (product name: Turbo Mill T250, manufactured by Turbo Kogyo Co., Ltd.) The obtained finely pulverized powder was classified with a multi-division classifier utilizing the Coanda effect to obtain core particles 21 having a weight average particle size (D4) of 6.8 μm.

[0086] (Production of toner particles 21) To 250.0 parts of ion-exchanged water heated to 40° C., 1.8 parts of tricalcium phosphate was added, and the mixture was stirred at a stirring speed of 15,000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to prepare an aqueous medium. The shell dispersion liquid 1 was added to the core particle 21 dispersion liquid at a solid content of 100.0 parts by mass. The mixture was added so that the total weight was 1.0 part. Sodium hydroxide solution was added while stirring at room temperature (about 25°C) and a rotation speed of 200 rpm to adjust the pH to 8.0. The mixture was then heated to 70°C and stirred for 2 hours to form a shell layer on the surface of the core particles. Next, the pH of the dispersion of toner particles was adjusted (neutralized) to 7 using hydrochloric acid, and the dispersion of toner particles was cooled to room temperature. After that, hydrochloric acid was added to dissolve calcium phosphate, which was a dispersant, and the mixture was filtered, washed with water, and dried to obtain toner particles 21 having a core-shell structure and a weight average particle size (D4) of 6.9 μm.

[0087] (Toner 21 Production) 100.0 parts of toner particles 21 and 1.5 parts of dry silica particles ("AEROSIL (registered trademark) REA90" manufactured by Nippon Aerosil Co., Ltd.: positively charged hydrophobically treated silica particles) were mixed for 3 minutes using an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.) to allow the silica particles to adhere to the toner particles 21. The mixture was then sieved through a 300 mesh (opening 48 μm) to obtain toner 21. The above evaluations were carried out using toner 21, and the obtained physical properties are shown in Table 4.

[0088] [Table 3]

[0089] [Table 4] In the table, the metal content indicates the polyvalent metal content P(M) (atomic %). The 30 μN storage modulus is the "surface storage modulus of the toner at a load of 30 μN at 25° C." The 50 μN storage modulus is the "surface storage modulus of the toner at a load of 50 μN at 25° C." The shell thickness is the average shell thickness (nm).

[0090] <Image evaluation> The image forming apparatus used was a Hewlett-Packard color laser beam printer (HP LaserJet Enterprise Color M652n), which was modified to have a process speed of 400 mm / sec. The cartridge used was an HP 656X genuine LaserJet toner cartridge (cyan). The product toner was removed from the inside of the cartridge, and after cleaning with an air blower, 300 g of the toner to be evaluated was filled in. The following evaluations were carried out using the image forming apparatus and cartridge described above.

[0091] [Fog] Fog was evaluated under a high temperature and high humidity environment (30°C / 80% RH). XEROX4200 paper (75 g / m2, manufactured by XEROX Corporation) was used as the evaluation paper. In a high temperature and high humidity environment, intermittent durability printing was performed in which two E character images with a print rate of 1% were output every four seconds, for a total of 20,000 sheets. Thereafter, a solid white image was output, the worst reflection density of the white background was designated as Ds, the average reflection density of the transfer material before image formation was designated as Dr, and Dr-Ds was designated as the fog value. The reflection density of the white background was measured using a reflection densitometer (Reflectometer Model TC-6DS, manufactured by Tokyo Denshoku Co., Ltd.) and an amber light filter was used. The smaller the value, the better the level of fogging. The evaluation criteria are as follows: (Evaluation Criteria) A: Less than 0.5% B: 0.5% or more but less than 1.5% C: 1.5% or more and less than 3.0% D: 3.0% or more

[0092] [Development streaks (developability)] Development streaks are vertical streaks of about 0.5 mm that occur due to crushing or cracking of toner, and are an image defect that is easily observed when outputting a full-surface halftone image. The development streaks were evaluated in a low temperature and low humidity environment (15° C. / 10% RH). XEROX4200 paper (75 g / m2, manufactured by XEROX Corporation) was used as the evaluation paper. In a low temperature and low humidity environment, 20,000 sheets of intermittent durability printing were performed, in which two E-letter images with a print rate of 1% were printed every four seconds. After that, a full-surface halftone image was printed, and the presence or absence of streaks was observed. The results are shown below. 5 As shown in. (Evaluation Criteria) A: Not occurred B: Development streaks occur in 1 to 3 places C: Development streaks occur in 4 to 6 places D: Seven or more development streaks or streaks 0.5 mm or wider

[0093] [Fixation] Solid image on transfer material (toner load: 0.9 mg / cm 2 ) were printed at different fixing temperatures and evaluated according to the following criteria. The fixing temperature was measured on the surface of the fixing roller using a non-contact thermometer. The transfer material was LETTER size plain paper (XEROX 4200, manufactured by XEROX, 75 g / m 2 ) was used. (Evaluation Criteria) A: No offset at 140℃ B: Offset occurs at 140℃ C: Offset occurs at 150℃ D: Offset occurs at 160℃

[0094] [Blocking (storage stability)] 5 g of each toner was placed in a 50 mL resin cup and left to stand for 3 days at a temperature of 55° C. and a humidity of 10% RH, and the presence or absence of aggregates was examined and evaluated according to the following criteria. (Evaluation Criteria) A: No clumps formed B: Slight clumps formed, crumbles when lightly pressed with fingers C: Agglomerates form, but do not crumble when lightly pressed with fingers D: Completely aggregated

[0095] [Examples 1 to 21] In Examples 1 to 21, the above evaluations were carried out using Toners 1 to 21, respectively. The evaluation results are shown in Table 5. In the following, Examples 16 and 19 will be referred to as Reference Examples 16 and 19, respectively.

[0096] [Comparative Examples 1 to 8] In Comparative Examples 1 to 8, the above evaluations were carried out using toners 22 to 29, respectively. The evaluation results are shown in Table 5.

[0097] [Table 5]

Claims

1. A toner comprising core particles having a resin component, a shell covering the surface of the core particles, and toner particles having a polyvalent metal, The resin component contains a polyester resin, The shell comprises an amino resin; the average thickness of the shell is 1.0 nm or more and 30.0 nm or less; In an electron image of a cross section of the toner particle taken using a transmission electron microscope, a content P(M) of polyvalent metals obtained by performing a line scan in a range of 0.85d to 1.15d from the outer periphery of a cross section of a toner particle toward a center of the toner particle in a direction perpendicular to the surface of the toner particle, where d (nm) is the thickness of the shell, is 0.0010 atomic % or more and 2.0000 atomic % or less; The toner is characterized in that, in nanoindentation measurement of the toner, the toner has a surface storage modulus of 6.50 GPa or more and 12.00 GPa or less at 25° C. under a load of 30 μN.

2. 2. The toner according to claim 1, wherein the surface storage modulus of the toner is 0.20 GPa or more and 12.00 GPa or less at 25° C. under a load of 50 μN in nanoindentation measurement of the toner.

3. 3. The toner according to claim 1, wherein the amino resin is a thermosetting resin.

4. 4. The toner according to claim 1, wherein the amino resin is at least one selected from the group consisting of a melamine resin, a urea resin, a guanamine resin and an aniline resin.

5. 5. The toner according to claim 1, wherein the polyvalent metal is at least one selected from the group consisting of Al, Mg, and Ca.

6. 6. The toner according to claim 1, wherein the polyvalent metal is Mg derived from magnesium hydroxide.

7. The method according to any one of claims 1 to 5, wherein the polyvalent metal is Al derived from aluminum sulfate. Toner included.

8. The toner according to any one of claims 1 to 5, wherein the polyvalent metal is Mg derived from magnesium chloride.

9. The toner according to any one of claims 1 to 8, comprising the toner particles and an external additive.

10. 10. The toner according to claim 1, wherein the amino resin is a melamine resin.

Citation Information

Patent Citations

  • Electrophotographic toner, its manufacturing method, electrophotographic developer and image forming method

    JP2006267527A

  • Method for manufacturing toner for nonmagnetic one-component electrostatic charge image development

    JP2008058620A

  • Toner for electrostatic charge image development

    JP2014164274A

  • Positively-charged toner

    JP2015022230A

  • Toner for electrostatic latent image development

    JP2015045844A